Embolic Materials: Understanding the Ocean of Choices - Shamar Young; Anthony S. Larson; Pooya Torkian; Jafar Golzarian (The Arab Journal of Interventional Radiology)
Embolization is a fundamental procedure that interventional radiologists perform on a daily basis to treat a variety of diseases. The disease processes for which embolization is considered a safe and effective treatment are continuously expanding, as are the embolization materials available for use. To achieve optimal clinical outcomes and minimize complications, it is imperative that the interventional radiologist understands the properties, strengths, and weaknesses of each class of embolic and specific embolic products. This is a continuous process as new materials are always becoming available. This article reviews the different classes of embolic materials, discusses strengths and weaknesses, and reviews areas of innovation.